THE EFFECTS OF MANIPULATING THE SYSTEM OPERATING PARAMETERS ON THE FUEL CONSUMPTION IN CO-GENERATION PLANT MODEL - Shah, Mohd. Halim; M. H. O, Hasinah (Jurnal Sains dan Teknologi Reaksi, 2003)
Co-generation can be classified as a clean technology in producing electricity now days, however it still produces carbon dioxides and carbon monoxides which directly related with the fuel consumption. Therefore, it is important to study the effect of changing the High Pressure Steam parameter in order to fully utilize fuel supplied while maintaining the power production of the plant. This research is based on data gathered from the actual Co-Generation Plant in Malaysia. The data gathered was used to develop the base case using HYSIS simulation and all the analysis is done using the result from the simulations. From the analysis it was found by manipulating the temperature of the High Pressure Steam will give appositive linear relation with a significant effect on the fuel consumption and power generated. However, by manipulating the pressure of the High Pressure Steam will not give a significant effect on the fuel consumption and power generated. As a conclusion, based on this study it can be said that by manipulating the High Pressure Steam temperature it will give a significant effect on the fuel consumption and power generated.